PROFITABILITY AND TAX AVOIDANCE: THE MODERATING EFFECT OF INDEPENDENT COMMISSIONERS - Azizi Rosida; Wahidatul Husnaini (ZILLZELL MEDIA PRIMA, 2024)
This research aims to empirically test the effect of profitability on tax avoidance, which independent commissioners moderate. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. The sample in this study was determined using a purposive sampling technique, which resulted in 485 observations. The research method used in this research is quantitative. Moderated Regression Analysis (MRA) tests the interaction effect of moderating variables. The research results show that profitability does not affect tax avoidance. Independent Commissioners cannot moderate the relationship between profitability and tax avoidance. The results of this study were unable to confirm agency theory. The limitation of this research is that not all hypotheses are supported. Further research can use measurements and other variables that influence tax avoidance.